Contribution of trunk swing to the performance of fixed-seat rowing - Lafreniere, Renee; Jensen, Matt; Smoljanovic, Tomislav; Wakeling, James M.; Klimstra, Marc; Thomas Orr, Rebecca; Pollock, Courtney L. (Frontiers in Sports and Active Living, 2025)
IntroductionThis study aimed to test the contribution of trunk swing to the performance during fixed-seat rowing in eligible and non-eligible (NE) para rowers. Assessment of trunk swing is used to classify para rowers with physical disability in Para Rowing (PR) 1 and PR2 rowers. PR1 rowers are classified based on the demonstration of impaired function of trunk swing.MethodsPR1, PR2, and NE rowers participated. Rowing ergometers were used in two different fixed-seating conditions, resulting in either (1) restricted trunk swing or (2) unrestricted trunk swing during the rowing stroke. Participants performed maximal effort 500 m pieces (race pace) in each seating configuration. Force production at the handle and fixed-seat rowing-specific trunk extension force was measured. Rowing performance measures were compared using a repeated-measures general linear model, including condition and group and an interaction between condition/group.ResultsOnly PR1 rowers generated greater trunk extension force during the restricted condition compared with the unrestricted trunk condition (P < 0.01). The restricted trunk swing condition resulted in a faster time to complete 500 m and minimal impact on force production for PR1 rowers. NE and PR2 rowers showed a significantly faster time to complete 500 m and greater stroke impulse (Ns) in the unrestricted compared with the restricted trunk swing condition (P < 0.01).DiscussionThese results provide evidence-based reasoning for the classification of fixed-seat rowers. Contrary to PR2 and NE rowers, whose rowing performance was decreased due to trunk restriction, PR1 rowers' performance benefits from the trunk restriction.